INTERNATIONALIZATION OF INDONESIAN AGRIBUSINESS: FOSTERING AGRIPRENEURS BY LEVERAGING FOOD QUALITY MANAGEMENT - Suprehatin Suprehatin (Jurnal Agribisnis dan Ekonomi Pertanian, 2009)
Food quality is becoming central issue for agribusiness actors as well as globalization and consumers’ concern about food safety and food standards’ rule. Thus, it is important for agripreneurs to manage their food quality to meet the consumer demand and to gain sustainable competitive advantage in the global food market. Based on literature review, this paper discusses the important of food quality management for Indonesian agripreneurs to develop a competitive position and expand their produce to global market. It is proposed that the necessary condition for fostering agripreneurs into global market is through the implementation food chain management.